PENGARUH MOTIVASI DAN KOMPETENSI SERTA LINGKUNGAN KERJA TERHADAP KINERJA TUTOR PENDIDIKAN KESETARAAN KELOMPOK BELAJAR UPTD. SKB - Choiriyah Choiriyah; Dendi Suhendar (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
The purpose of this research are knowing and analyizing about The Effects of Motivation, Competence and Work Enviroment together and partially on performance of education tutor in study groups were fostered by UPTD SKB Musi Banyuasin. The population of tutor in this research are 50 peoples. Thinking about the small number of the population, the author use census method which is all of the population in this research be research sample. The result of this research can be concluded that the value of calculated F for motivation, competence, work environment on the performance of tutors is 9.098. While the F table with a significance level (α) = 5% by the denominator (nk-1) = (50-3-1) and the numerator (k = 3) is 2.807. If the calculated of F ≥ F table, Ho is rejected and Ha accepted. Thus the F-test analysis results of this study it can be concluded that the calculated F ≥ F 9.098 2.807 table which means, there is a significant effect of motivation, competence, and the work environment  jointly on the performance of tutors. Whereas, the value of t is for motivation on the performance of tutors  is the value of t 0.567t <t table 2.013. So, Ho accepted and Ha rejected, which means there is no significant effect of motivation variable to variable performance tutor. T value for competence on the performance of tutors is the value of t 2,979 ≥ t table 2.013. So, Ho is rejected and Ha is accepted, which means that there is a significant effect of competence  on the performance of tutors. T value for the working environment on the performance of tutors (Y) is the value of t 2.104 ≥ t table 2.013. So, Ho is rejected and Ha is accepted, which means that there is a significant effect of the work environment variables to tutor performance variable.